Meningkatkan Keterampilan Shooting Bola Basket Dengan Konsep Beep Pada Siswa SMP - Isdwimanto, Isdwimanto (Educatio, 2019)
This study aims to describe the extent of improvement in basketball shooting skills with the BEEF concept in students of class VII 6 of SMP Negeri 1 Pringgasela. This study uses a qualitative approach and the type of research conducted is classroom action research. This research was conducted in SMP Negeri 1 Pringgasela from October to November 2017 in 2 cycles. The results of this study indicate that on the first cycle there is an increase based on the pretest value obtained but not too significant so that it is resumed in cycle II to be improved with significant results on basketball shooting skills with the BEEF concept. Obtained an increase in each cycle already above 15% with an average increase for all compones of 30.35%.